Modular mobile pool structural & filtration system for military training and fitnest test / Prof. Madya Ts. Dr. Rostam Yaman ... [et al.] - Yaman, Rostam; Muhamad Arif, Nor Rima; Kaliwon, Julaida; Aris, Nurul Nabilah; Ismail, Farrah Zuhaira; Mohamed Ishak, Norishahaini; Ab Aziz, Ali Zakafri; Abdul Malik, Muhammad Abdul Qahhar; Rahim, Mohd Rowfiq; Mat Saad, Norizwan; Zulkifli, Khairul Anuar; Ya'akub, Mohammad Sukri; et al. (College of Built Environment, 2023)
Military training and periodical assessment is important in preparing a well built soldier physically and mentally.